When Did the Paleotethys Ailaoshan Ocean Close: New Insights From Detrital Zircon U‐Pb age and Hf Isotopes. Issue 5 (22nd May 2019) - Xu, Jian; Xia, Xiao‐Ping; Lai, Chunkit; Long, Xiaoping; Huang, Chao
Abstract: We present new laser ablation (LA)‐multicollector‐inductively coupled plasma mass spectrometry detrital zircon U‐Pb age and Hf isotope data of the Triassic sedimentary rocks from the eastern and western sides of the Ailaoshan suture in SW China, which separate the Indochina and South China blocks. Detrital zircon grains of the Lower‐Middle Triassic sequences from western South China show single age population of 280–237 Ma (peak at 254–251 Ma) with mainly positive ε Hf( t ) values (+0.15 to +9.11, 60%). The Middle Triassic samples from eastern Indochina also contain single age population of 273–236 Ma (peak at 246–242 Ma), but with mainly negative ε Hf( t ) values (−18.95 to −1.83, 88%). The unimodal detrital zircon age pattern and Hf isotope features suggest that the Permian‐Triassic magmatic arcs had supplied detritus for the Lower‐Middle Triassic sequences on both sides of the Ailaoshan suture. In contrast, the Upper Triassic sequences on the either side of the suture display similar polymodal age populations at 290–230, 500–400, 850–700, 1000–900, 2000–1800, and 2600–2400 Ma. This indicates a dramatic change in detrital provenance across the Middle‐Late Triassic boundary. We interpret this change to be resulted from the closure of the Paleotethyan Ailaoshan Ocean in the early Late Triassic. The ocean closure and consequent Indochina‐South China continent‐continent collision may have connected the drainage systems of the two blocks, leading to the marked similarities in their post‐Middle Triassic sedimentary provenance. Key Points: Lower‐Middle Triassic sedimentary rocks received detritus from Permian‐Triassic magmatic arcs Upper Triassic sedimentary rocks received detritus from both the Indochina‐South China interior and the Permian‐Triassic magmatic arcs Final closure of the Ailaoshan Ocean was likely completed by the Late Triassic